Drug utilization review of systemic antifungals in a tertiary care hospital in the Philippines - Aguila, Johanna Alyssa V.​; Cruz, Seth Lawrence F.​; Reyes, Jan Gabrielle M.​; Peña, Imelda G.​ (Manila College of Pharmacy, University of the Philippines, 2019)
Inappropriate antifungal use has been linked to rising rates of antifungal resistance and has contributed to increased morbidity and mortality, as well as a shift in the etiology of invasive fungal infections. However, documentation on inappropriate prescribing for antifungals in the country is lacking. To evaluate the use of systemic antifungals in a tertiary care hospital in the Philippines, a retrospective medication chart review was conducted; clinical treatment guidelines were used in assessing appropriateness of use. Fluconazole was identified to be the primary antifungal agent in all 67 patient cases; prophylaxis was the most employed therapeutic regimen. Antifungal prescriptions had an overall mean appropriateness of use point score of 8.55±1.38; targeted therapy had the highest score (9.54±0.97), followed by empirical (8.65±0.99), and prophylaxis (8.16±1.50). Inappropriateness of antifungal use with regards to dosing, duration, and indication were the causes of inappropriate prescription. Inappropriate use may result in resistance, adverse treatment outcomes, and increased costs. Development of resistance is particularly a risk when using low doses of fluconazole for prolonged durations, which was rampant in prophylactic regimens. The overall use of fluconazole in the tertiary care hospital for the six-month period was found to be 19.5 DDDs per 100 patient days, with the parenteral formulation (5.8 DDDs) of fluconazole 200 mg having slightly higher DDDs than its oral counterpart (5.4 DDDs). Total DDDs per 100 patient days was similar to that of hospitals in other countries, although higher than those with strict antifungal stewardship programs. Monitoring of antifungal prescriptions is necessary to optimize use in the hospital setting.
​Thesis (Bachelor of Science in Pharmacy)--University of the Philippines, June 2019.
Keywords: Drug utilization; Antifungal agents